2003
DOI: 10.1093/jn/133.1.148
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and Conversion of 11,12-3H-β-Carotene to Vitamin A in Sprague-Dawley Rats of Different Vitamin A Status

Abstract: The aim of this study was to determine the bioavailability and bioconversion to vitamin A of a single oral dose in oil or an aqueous dispersion of labeled beta-carotene in rats of different vitamin A status. Weanling Sprague-Dawley rats were fed a vitamin A-deficient diet and supplemented for 4 wk with 0, 7, 21 and 63 micro g/(rat. d) of retinyl acetate. The rats, of different vitamin A status, were then given a single oral dose of 11,12-(3)H-beta-carotene (0.15 micro mol) dissolved in corn oil or dispersed in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The procedure for the extraction of retinoids in liver, other tissues and feces was essentially the same as published before [24]. The dried extract was dissolved in 2-propanol/ dichloromethane (2:1, v/v; 100 to 500 l).…”
Section: Retinoids Analysis In Liver and Other Tissues Feces And Urinementioning
confidence: 99%
“…The procedure for the extraction of retinoids in liver, other tissues and feces was essentially the same as published before [24]. The dried extract was dissolved in 2-propanol/ dichloromethane (2:1, v/v; 100 to 500 l).…”
Section: Retinoids Analysis In Liver and Other Tissues Feces And Urinementioning
confidence: 99%
“…In addition, note that other authors have not observed this regulation either. [24,25] Thus, we hypothesize that other(s) factor(s) which are different in these different studies, likely play a role in this regulation. [44] Concerning the effect of VA status on intestinal metabolism of VA in females, it is interesting to note that, as observed for gene expression, there were apparent U-shaped responses regarding the effect of VA status on 𝛽-carotene and retinyl palmitate responses.…”
Section: Discussionmentioning
confidence: 85%
“…[20][21][22] Furthermore, it was recently shown that the catalytic activity of lecithin retinol acyltransferase (LRAT) coordinates this regulation. [23] However, Goswami et al [24] did not observe an effect of the VA status on 𝛽-carotene absorption and conversion to VA in rats. Furthermore, Lemke et al [25] observed a lower conversion efficiency of 𝛽-carotene after VA supplementation in two women, which agrees with the regulatory network, together with a higher absorption efficiency of 𝛽-carotene in these volunteers, which apparently disagree with this network.…”
Section: Introductionmentioning
confidence: 95%
“…Carotenoids labelled with a radioisotope like 3 H or 14 C have been prepared from a labelled precursor by biosynthesis in various organisms and plants. 1 4-8 The synthesis of carotenoids specifically labelled with isotopic carbon and tritium has been reviewed.…”
Section: Introductionmentioning
confidence: 99%
“…We have used this preparation successfully in studying the bioavailability of b-carotene and its conversion to vitamin A in rats. 14 Retinoids are unstable towards light, heat and air. To reduce losses of the tiny amount of the starting material, [11,12-3 H]-retinol, and for ease of handling, [11,12-3 H]-retinol was diluted with unlabelled retinol to give tracer labelled [11,12-3 H]-retinol.…”
Section: Introductionmentioning
confidence: 99%